2008
DOI: 10.1152/ajpgi.00549.2007
|View full text |Cite
|
Sign up to set email alerts
|

Obestatin inhibits motor activity in the antrum and duodenum in the fed state of conscious rats

Abstract: Obestatin is a novel peptide encoded by the ghrelin precursor gene; however, its effects on gastrointestinal motility remain controversial. Here we have examined the effects of obestatin on fed and fasted motor activities in the stomach and duodenum of freely moving conscious rats. We examined the effects of intravenous (IV) injection of obestatin on the percentage motor index (%MI) and phase III-like contractions in the antrum and duodenum. The brain mechanism mediating the action of obestatin on gastroduoden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 24 publications
2
66
1
4
Order By: Relevance
“…Functional gastrointestinal disorders (FGIDs) are characterized as 16 chronic or recurrent GI symptoms, which are not explained by structural or biochemical abnormalities. Brain-gut interaction plays an important role in the pathophysiology of FGIDs [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional gastrointestinal disorders (FGIDs) are characterized as 16 chronic or recurrent GI symptoms, which are not explained by structural or biochemical abnormalities. Brain-gut interaction plays an important role in the pathophysiology of FGIDs [44].…”
Section: Discussionmentioning
confidence: 99%
“…Gastric motility was measured by manometric methods described in previous study [16]. Conscious animals without fasting were put in wire-bottom and non-restraint polycarbonate cages.…”
Section: Manometric Recordingsmentioning
confidence: 99%
“…This seems to be an indirect effect mediated via the hypothalamus by the activation of anorexigenic cocaine-and amphetamineregulated transcripts as well as urocortin gene expression (Asakawa et al 2005). Similarly, obestatin has also been described as an inhibitor of motor activity in the gastroduodenal region in the fed state, but not in the fasted state, an effect that seems to be an indirect action in which CRH type 1 and type 2 receptors might be involved (Ataka et al 2008). However, obestatin was unable to antagonize AG-induced stimulation of gastroduodenal motility (Ataka et al 2008).…”
Section: Nonendocrine Actionsmentioning
confidence: 99%
“…Similarly, obestatin has also been described as an inhibitor of motor activity in the gastroduodenal region in the fed state, but not in the fasted state, an effect that seems to be an indirect action in which CRH type 1 and type 2 receptors might be involved (Ataka et al 2008). However, obestatin was unable to antagonize AG-induced stimulation of gastroduodenal motility (Ataka et al 2008).…”
Section: Nonendocrine Actionsmentioning
confidence: 99%
“…Peripheral obestatin inhibits gastric emptying. Obestatin has clearly been shown to act via the corticotropinreleasing factor (CRF) receptor subtypes 1 and 2 in the brain to inhibit motor activity in the antrum and duodenum in conscious fed rats (57). However, other studies have shown that obestatin does not affect gastric and intestinal motility in vivo or in vitro (58)(59)(60).…”
Section: Ghrelin and Metabolismmentioning
confidence: 99%